2018
DOI: 10.1037/adb0000392
|View full text |Cite
|
Sign up to set email alerts
|

Affect, craving, and cognition: An EMA study of ad libitum adolescent smoking.

Abstract: Reducing smoking among adolescents is a public health priority. Affect, craving, and cognitive processes have been identified as predictors of smoking in adolescents. The current study examined associations between implicit attitude for smoking (assessed via the positive-negative valence implicit association test) and affect, craving, and smoking assessed using ecological momentary assessment (EMA). Adolescent smokers (n = 154; Mage = 16.57, SD = 1.12) completed a laboratory assessment of implicit smoking atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 81 publications
1
15
0
Order By: Relevance
“…Specifically, the number of smoked cigarettes increased with both craving and positive affect on the same day. These findings are in accordance with the results from an earlier EMA study with a higher compliance rate [22].…”
Section: Plos Onesupporting
confidence: 93%
See 1 more Smart Citation
“…Specifically, the number of smoked cigarettes increased with both craving and positive affect on the same day. These findings are in accordance with the results from an earlier EMA study with a higher compliance rate [22].…”
Section: Plos Onesupporting
confidence: 93%
“…Effects of tDCS on addictive behaviour have often been measured with retrospective self-reports in the lab. Since craving and substance use are both episodic phenomena that are associated with affect and context [22][23][24], measuring these variables in daily life may lead to more reliable answers. Furthermore, retrospective measurements may be influenced by recall biases [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Across the 8 studies, the average compliance rate was 78.4% (SD = 8.3) with a range from 70 to 91%. Shiffman et al (2002) found no relation between momentary positive affect and smoking, whereas Dvorak et al (2018) reported an association between momentary positive affect and momentary smoking. Single studies found a negative association between momentary positive affect and stress and internalizing problems (South and Miller 2014) and sedentary behavior (Elavsky et al 2016).…”
Section: Findings Of Studies Using Other Ema Data Collection Devicesmentioning
confidence: 90%
“…The search to EMA studies that used palm tops, PDAs or other EMA devices to assess well-being multiple times a day resulted in 8 studies that included healthy participants (Dvorak et al 2018;Elavsky et al 2016;Ilies et al 2010;Johnston et al 2013;Juth et al 2015;Shiffman et al 2002;South and Miller 2014;Yip 2005) (see supplementary data Sheet 3 for details of the studies and the results).…”
Section: Findings Of Studies Using Other Ema Data Collection Devicesmentioning
confidence: 99%
“…The advantages of the EMA approach over retrospective self-reporting include more accurate tracking of smoking frequency and patterns, more detailed capturing of smoking cravings, and high ecological validity of the data ( 65 67 ). Since both craving and substance use are situational phenomena related to emotion and environment ( 68 70 ), measuring these variables in daily life may lead to more reliable answers. Therefore, in this study, EMA was used to assess daily craving changes and smoking behavior in real-time.…”
Section: Introductionmentioning
confidence: 99%